Imagining Out of Hope. - Humbert-Droz, Steve; Vazard, Juliette (Philosophical Quarterly, 2025)
Both lay people and philosophers assume that hoping for something implies imagining it. According to contemporary philosophical accounts of hope, hope involves an element of imagination as input, part, or output of hope. However, there is no systematic view of the interaction between hope and the different processes constituting imagination. In this paper we put forward a view of (i) the kind of imaginings typically triggered by hopeful states, (ii) the nature of the interaction between hope and hopeful imaginings, and (iii) the epistemic value of imagining out of hope. We argue that a paradigmatic output of hope is an immersive kind of cognitive imagination. Additionally, justified hopes constrain our immersive imaginings in such a way as to provide them with a specific epistemic value. Hopeful imaginings are not mere fantasies or wishful thinking; they constitute valuable experiences we can learn from and rely on in planning our future.